2010
DOI: 10.1111/j.1439-0418.2010.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance of Cry1Ab‐selected Asian corn borer to other Cry toxins

Abstract: The Asian corn borer, Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae), is the most important insect pest of maize in China. Despite the proven track record of biotech Bacillus thuringiensis (Bt) maize to provide an effective means to control lepidopteran pests such as the European corn borer Ostrinia nubilalis (Hübner), these crops have not been commercialized in China. However, Cry1Ab‐ and Cry1F‐expressing maize derived from genetic transformation events MON810 (Monsanto), Bt11 (Syngenta) and TC1507 (Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 68 publications
3
55
1
Order By: Relevance
“…The present results also demonstrate that Cry1Ab and Cry1F have high affinity to different protein receptors, thus supporting the observation of low cross resistance levels from Cry1Ab to Cry1F in O. furnacalis and O. nubilalis (Siqueira et al, 2004a;Xu et al, 2010). Furthermore, it has been reported that Cry1Ab shares a low affinity receptor with Cry1F in O. nubilalis (Hua et al, 2001).…”
Section: Discussionsupporting
confidence: 68%
“…The present results also demonstrate that Cry1Ab and Cry1F have high affinity to different protein receptors, thus supporting the observation of low cross resistance levels from Cry1Ab to Cry1F in O. furnacalis and O. nubilalis (Siqueira et al, 2004a;Xu et al, 2010). Furthermore, it has been reported that Cry1Ab shares a low affinity receptor with Cry1F in O. nubilalis (Hua et al, 2001).…”
Section: Discussionsupporting
confidence: 68%
“…The levels of Cry1Ie2 toxicity to O. nubilalis neonates were comparable to those reported for the Cry1Ab (41,42) and Cry1Fa (5,40) toxins. This similar toxicity is also indirectly supported by reports of a lack of significant differences (based on overlapping confidence intervals) in Cry1Ie1, Cry1Ab, and Cry1Fa toxicity to O. furnacalis (14) and the same toxicity to Ostrinia species larvae observed for the Cry1Ie1 and Cry1Ie2 toxins in the present study. The new Cry1Ie2 toxin was expressed in E. coli cultures as a protoxin of 81 kDa, a molecular mass uniquely common to other Cry1I toxins (11,12).…”
Section: Discussionsupporting
confidence: 77%
“…These observations are in contrast to a previous report on Cry1Ia7 toxin activity against noctuid larvae (11) but in agreement with bioassay data on Cry1Ie toxins (12). High Cry1Ie activity against Ostrinia species explains why Cry1Ie1-expressing maize effectively suppressed O. furnacalis in field trials (14). Taken together, our bioassay data support a restricted range of Cry1Ie2 activity against lepidoptera yet high activity against key Ostrinia pest species.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast, interaction was shown between Cry1Ab and cadherin for both resistant and susceptible O. nubilalis (Siqueira et al 2006;Flannagan et al 2005). Despite the possibility that Cry1F and Cry1Ab toxins share receptor sites on O. nubilalis cad and apn1 proteins, the laboratory-selected Cry1Ab-resistant strains shows low cross-resistance to Cry1F toxin (Siqueria et al 2004) as did the O. furnicalis ACB-AbR strain (Xu et al 2010). Furthermore, cad and apn1 loci do not co-segregate with an O. nubilalis Cry1Ab trait from a colony that shows [2,500-fold increase in resistance (Coates et al 2008a), which that alleles at these loci do not contribute to larval Cry1Ab resistance traits.…”
Section: Mapping Of the Larval O Nubilalis Cry1f Resistance Traitmentioning
confidence: 82%